Classification and analysis of the Maximum Power Point Tracking algorithms of Photovoltaic Systems - زينه, عهد (Latakia University Journal -Engineering Sciences Series, 2020)
The article discusses the maximum power point tracking methods of photovoltaic systems, Mechanics and Electronics, and provides a classification of electronic MPPT algorithms into three main categories: Independent of the photovoltaic panel, Related to the photoelectric panel, Hybrid algorithms. This study can provide a reference for the solution of the weak point of PV systems, which is the low efficiency of converting solar radiation to electrical energy through PV cells and the nonlinear behaviour of PV systems as well as changes in the maximum power according to the level of solar radiation and temperature. The research presents the most popular MPPT methods, the working principle, features and disadvantages of each application, and summarizes the results of comparison of MPPT types of algorithms in terms of class and application (digital, simulated), sensitivity parameters, speed of convergence, accuracy and complexity. The research analyses the effect of the implementation of these algorithms on raising the dynamic response of the PV system to changes in temperature and radiation by simulating the parts of the studied system in the Matlab / Simulink environment. Simulation and practical results show the priority of some algorithms for others in terms of efficiency and dynamic response against sudden changes in solar radiation and temperature.